Analisis Energi terhadap Performa Boiler Tipe Fluidized Bed Combustion - Maedanu Fasola Putra; Danar Susilo Wijayanto; Nugroho Agung Pambudi (Jurnal Mekanika dan Sistem Termal, 2016)
The research aims to investigate the condition of Basuki boiler based on the energy analysis result. The research used quantitative-descriptive method. The population of this research was daily record of Basuki boiler. The sample was daily record of Basuki boiler performance for 1 year (February 2015 to January 2016). The sample was taken using purposive sampling method. The research analyzed energetic efficiency and heat losses were included. Based the result of the research, it can be concluded that Basuki boiler condition based on its energy analysis was good, because the energetic efficiency (83,14%) was higher than the company’s target (80%). Total heat losses occured during boiler operation at 16,86% was devided into (1) heat loss in the flue gas (5,15%); (2) heat loss caused by unburned H2 gas (5,47%); (3) heat loss caused by water content in the fuel (1,50%); (4) heat loss caused by the humidity (0,58%); (5) heat loss caused by imperfect combustion (0,13%); (6) heat loss caused by radiation and indeterminable heat loss (4,03%).